Remapping the Terrain School Size, Cost, and Quality - Nachtigal, Paul. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1992)
The usual opposing perspectives on the school-size debate focus on economies of scale and school climate. This paper examines school size, educational cost, and quality from a third perspective, that of maintaining healthy viable communities. Rural schools and rural communities are tightly linked and highly interdependent. The school is one of the largest economic enterprises in many rural communities and is often the only viable public service agency. Nevertheless, for many rural communities, public education becomes a one-way flow of resources as educated young people leave to find employment elsewhere. Eventually, the community withers and dies. It is apparent that rural education must be redesigned to be of high quality and yet not extractive of human resources in support of the urban labor force, and that the notion of educational cost effectiveness must be recast in terms that include community development. One approach to involving schools in community development is to use the community as a focus of study. The local environment becomes a part of the school curriculum, a laboratory for learning about the real world. At the same time, student projects may return immediate benefits to the community. With this approach, "costs" become investments in the community's future. Where larger numbers would produce economies of scale, these economies can be realized by forming clusters of schools to share resources. The different educational functions of the school district may be separated and reorganized to increase efficiency. An appendix gives examples of clustering. (SV)
ERIC Note: In: Source Book on School and District Size, Cost, and Quality, see RC 019 318.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Community Development; Consolidated Schools; Cost Effectiveness; Educational Quality; Elementary Secondary Education; Rural Areas; Rural Development; Rural Education; Rural Schools; School Closing; School Community Relationship; School Size; Shared Resources and Services; Community Viability; Cluster Schools; Information Analyses; Opinion Papers